Conflicts of international and national customs law with EU customs law: the example of the Republic of Lithuania - Valantiejus, Gediminas; Валантиеюс, Г.; Валантиєюс, Г. (Одеса : Гельветика, 2020)
The article examines the functioning of the modern customs regulatory environment for the EU Member States, which is composed of three levels of sources: international legal instruments, EU primary and secondary legislation and national legislation of individual Member States. However, the practical application of these provisions is related to conflicts between the sources of national and international law and even the different sources of international law itself. It should be noted that at the present time, individual states have not yet formed a unified approach on whether the WTO Agreements should have a direct effect in their national legal system, as most of the states are following the doctrine of dualism and deny this possibility, although the practices followed by the national courts of the Republic of Lithuania have shown the elements of a monistic approach to this problem. The increasing use of international preferential trade agreements and the prevalence of agreements, which establish the customs unions, could also be regarded as a challenge to the development of international economic law and international trade system. Moreover, analysis of the judicial practices of national courts (in the Republic of Lithuania) and the case-law of the Court of Justice of the European Union has confirmed that an explicit approach to the relationship existing between international, EU and national customs law has not yet materialized.
Valantiejus G. Conflicts of international and national customs law with EU customs law: the example of the Republic of Lithuania / G. Valantiejus // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". – Одеса : Видавничий дім «Гельветика», 2020. - № 2. – C. 30 - 41.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; international trade; international customs law; World Trade Organization Agreements; Union Customs Code; Republic of Lithuania; міжнародна торгівля; міжнародне митне право; угоди СОТ; Митний кодекс ЄС; Литовська Республіка; международная торговля; международное таможенное право; соглашения ВТО; Таможенный кодекс ЕС; Литовская Республика